Independent validation of the Pain Management Plan in a multi-disciplinary pain team setting. Issue 4 (November 2016) - Quinlan, Joanna; Hughes, Richard; Laird, David
Context/background: The Pain Management Plan (PP) is a brief cognitive behavioural therapy (CBT) self-management programme for people living with persistent pain that can be individually facilitated or provided in a group setting. Evidence of PP efficacy has been reported previously by the pain centres involved in its development. Objectives: To provide a fully independent evaluation of the PP and compare these with the findings reported by Cole et al. Methods: The PP programme was delivered by the County Durham Pain Team (Co. Durham PT) as outlined in training sessions led by Cole et al. Pre- and post-quantitative/patient experience measures were repeated with reliable and clinical significant change determined and compared to the original evaluation. Results: Of the 69 participants who completed the programme, 33% achieved reliable change and 20% clinical significant change using the Pain Self-Efficacy Questionnaire (PSEQ). Across the Brief Pain Inventory (BPI) interference domains between 11% and 22% of participants achieved clinical significant change. There were high levels of positive patient feedback with 25% of participants scoring 100% satisfaction. The mean participant satisfaction across the population was 88%. Conclusion: The results from this evaluation validate those reported by Cole et al. It demonstrates clinically significant improvement in pain and health functioning and high patient appreciation results. Both evaluations emphasise the potential of this programme as an early intervention delivered within a stratified care pain pathway. This approach could optimise the use of finite resources and improve wider access to pain management.